Managing Multitype Capacity Resources For Frequency Regulation In Unit Commitment Integrated With Large Wind Ramping - Hemmati, Reza; Mehrjerdi, Hasan; Shafie-khah, Miadreza; Siano, Pierluigi; Catalao, Joao P.S. (IEEE, 2020)
An efficient unit commitment planning must consider frequency regulation capacity in the model. Such models are more complicated under a high penetration level of renewable energy because of renewable ramping and uncertainty. This paper addresses these issues in the unit commitment. The proposed model for unit commitment considers uncertainty and ramping of wind power, frequency regulation capacity, spinning reserve, demand response, and pumped-storage hydroelectricity. In order to optimize the costs, the pumped-storage hydroelectricity and demand response program are also included to deal with ramping and uncertainty. The numerical results specify that the arrangement of frequency regulation capacity, pumped-storage system and demand response can effectively tackle both the ramping and uncertainty. The system includes 10-generator with total power equal to 1070 MW and one wind generator with 300 MW power. The initial wind integration level is about 28%. It is verified that decreasing the frequency regulation capacity by 10% reduces wind integration level by 94%. The demand response and pumped-storage increase wind integration level by 10% and 16%; while both together increase wind integration by 25% compared to the initial level. The wind integration level without large wind ramping can be increased up to 200%.
Keywords: Capacity planning; Frequency control; generators; Load management; uncertainty; wind energy; fi=Sähkötekniikka|en=Electrical Engineering|